Management of stress amongst state universities’ lecturers for improved performance: A quantitative approach - Udodiugwu, Michael Ikenna (Annals of Human Resource Management Research, 2024)
Purpose: This study aimed to assess the influence of stress on the performance of state university lecturers in the Southeast, Nigeria. Research Methodology: To achieve this, a correlational survey design method was employed. The study encompassed all six state universities in southeastern Nigeria, focusing exclusively on academic staff. This research involved all state university lecturers on full-time appointments, ranging from professorial cadres to graduate assistants. Data were obtained from personnel offices of the six state universities under review. The social sciences statistical package was used to analyze the data and draw conclusions. Results: The study revealed a significant positive impact of work-life balance on career development, as well as a marked positive impact of mental health management on the academic productivity of state university lecturers in southeast Nigeria. Limitations: The study focused solely on the impact of stress among lecturers of state universities in southeast Nigeria and was limited to the six state universities approved by the National Universities Commission as of the 2023/2024 academic session. Contribution: This study contributes to existing knowledge by introducing new indicators, such as work-life balance and mental health management, to the theme of stress management. It also adds to the empirical and theoretical evidence that could aid future scholars in exploring stress management further. Funding: This research was funded by the authors, and no external funding was received from any institution or corporate entity during this study.